Contemporary and 'Messy' Rural In‐migration Processes: Comparing Counterurban and Lateral Rural Migration. Issue 6 (1st June 2015) - Stockdale, Aileen
Abstract: This paper questions the ongoing dominant coverage given to counterurbanisation in the rural population literature. It is argued that this provides only a partial account of the true diversity of contemporary migration processes operating in rural areas and has the potential to fuse together different in‐migration processes. Specifically, lateral rural migration has been under‐researched to date. Using empirical data from a survey of 260 migrant households to 3 UK case study areas (in Scotland, Wales, and Northern Ireland), the significance of lateral rural migration is revealed and compared with counterurban migration and migrants. The last change of address shows that 59% relocated from an urban area (participating in a counterurban flow) whilst 41% moved from another rural location (lateral rural flow). The boundary between migration processes can, however, be blurred: Some moves are an example of both counterurbanisation and lateral rural flows. Incorporating lifetime migration histories data demonstrates the contemporary complexity and messiness of rural in‐migration processes. For example, 26% of these migrant households only ever undertook a lateral rural move during their lifetime. For others, the direction of migration has changed numerous times and intertwined with each move are aspects of life course, return, and inter‐regional migration. Comparing the survey characteristics and motivations of counterurban and lateral rural migrants, alongside interview material, highlights important similarities and differences. The paper concludes by calling on rural population geographers to more fully engage with the complexity, totality, and indeed messiness of contemporary rural in‐migration processes. © 2015 The Authors. Population, Space and Place . Published by John Wiley & Sons, Ltd.